An abc Proof Too Tough Even for Mathematicians - Hartnett, Kevin (The Best Writing on Mathematics 2013, 2014)
On August 30, 2012, a Japanese mathematician named Shinichi Mochizuki posted four papers to his faculty website at Kyoto University. Rumors had been spreading all summer that Mochizuki was onto something big, and in the abstract to the fourth paper Mochizuki explained that, indeed, his project was as grand as people had suspected. Over 512 pages of dense mathematical reasoning, he claimed to have discovered a proof of one of the most legendary unsolved problems in math. The problem is called the abc conjecture, a 27-year-old proposition considered so impossible that few mathematicians even dared to take it on. Most